MARKETING ORIENTATION AND BUSINESSPERFORMANCE OF SMALL SCALE INDUSTRIAL RUBBER SECTOR IN SRI LANKA - Samarasinghe, D.S.R. (My University, 2016)
Attached

Marketing orientation, if.interpseted as the marketing concept, could reflect along a variety of dimensions such as orientation towards customer focus, market focus, marketing mix focus and strategy focus. With its significance in the field of marketing, literature on marketing orientation has consistently supported the notion that paying a substantial level of attention to marketing orientation will esult in an increased performance of a business. Accordingly, the present study addresses the gap in the literature by promoting the research objective of establishing a predictive positive relationship of market orientation with business performance of the small scale rubber products manufacturing industries. The industrial rubber products sector of Sri Lanka provides a very less researched area in the field of marketing, and the issue regarding its attributed market orientation has never been probed before. Marketing orientation in conjunction with other commonly associated constructs such as .narketing awareness, environmental forces, and entrepreneurial characteristics was incorporated in a conceptual model that related all variables to business performance. In accordance with the framework, direct effects of marketing orientation, marketing awareness, competition, technology, government support, and entrepreneurial characteristics were hypothesized to have influence on business performance. An adequate sample of 70 small scale rubber products manufacturing industries was selected from a population of 89. A questionnaire was administered to collect data, with a follow -up interview with the entrepreneurs. Data was evaluated using descriptive analysis as well as multivariate analysis. Multiple regression model with stepwise regression has provided significant statistical supports for the acceptance of having market orientation and marketing awareness closely associated with the business performance of the industrial rubber products sector. Accordingly, the study has empirically established that there are positive relationships of marketing orientation and marketing awareness with business performance. The best predictor of business performance of industrial rubber products has been the marketing awareness. Marketing orientation has become a less significant predictor while variables of environment forces, and entrepreneurial characteristics as predictors of business performance have been rejected. The findings have directly and indirectly generated many managerial implications, and also PIQYided many research implications to be considered in a future work.